Nanoemulsion of Cardamom Fruit Extract (Amomum compactum) and its Characterization - Ina, Febi Rambu; Saragih, Horasdia (Jurnal Biologi Tropis, 2025)
The development of medicinal materials from bioactive compounds of plants continues to be carried out. Various problems that occur in it continue to be overcome. Bioactive compounds of plants are known to be hydrophobic, including bioactive compounds from cardamom fruit, so that these compounds are difficult to deliver into the organs of the body. To overcome this problem, nanoemulsion techniques have been carried out. The purpose of this study was to produce nanoemulsions of bioactive compounds of cardamom fruit and to study their characteristics. Nanoemulsions of bioactive compounds of cardamom fruit have been synthesized using a microtube equipment system by utilizing the characteristics of the flow pattern of its liquid segment which is circulative forming a vortex in a very small size. The nanoemulsions obtained have a diameter ranging from 15.2 nm to 19.7 nm. The diameter increases when the mass of the bioactive compound concentrate of cardamom fruit is increased. The polydispersity index ranges from 0.341 to 0.637; the average electrophoretic mobility ranges from -0.000010 cm2/V.s to -0.000062 cm2/V.s and the zeta potential from -1.3 mV to -8.1 mV. From the results obtained, it shows that the obtained nanoemulsions have a relatively very small average diameter, their size distribution is relatively heterogeneous and the surface charge surrounding the nanoemulsions is negative. However, the zeta potential is still relatively small so that it has the potential to be less stable. Therefore, an effort to increase the magnitude of the zeta potential in the future needs to be done.